Sistem Informasi Simpan Pinjam Dan Pengelolaan Hasil Pertanian Bumdes Baru Kabupaten Barito Selatan Berbasis Website - Sari, Nova Noor Kamala; Olpah, Syahrida (Journal of Information Technology and Computer Science, 2022)
BUMDes Baru is a village-owned enterprise established with the intention to improve the welfare of the people of Desa Baru through its main program, namely savings and loans, as well as additional programs in the form of management of agricultural products and village markets. Currently, all activities including savings and loans transactions, PKR levies, facility rentals and making monthly reports for BUMDes are still carried out manually. This resulted in people having to come to the BUMDes secretariat repeatedly in order to take care of loan applications. Therefore, a Website-Based Information System for Savings and Loans and Management of Agricultural Products of New Village-Owned Enterprises (BUMDes) of South Barito Regency was created.. The methodology used in the Savings and Loans Information System and Agricultural Product Management of the New BUMDes is waterfall, with stages, namely the Requirements Definition stage which is carried out in making business process designs and flowcharts, System and Software Design is carried out in making Data Flow Diagrams, Entity Relationship Diagrams, Databases and Interface Design, Implementation and Unit Testing with the programming languages ​​used, namely PHP, Javascript, PhpMyAdmin and Integration and System Testing using the Blackbox Testing method. This website is intended to facilitate the public in seeking information about the New BUMDes, facilitating members in conducting savings and loan transactions, leasing facilities and kiosks, PKR retribution transactions, and facilitating the management of BUMDes to be more organized and detailed.